Ketersediaan dan Serapan Ca Pada Kacang Tanah di Tanah Alfisols yang Diberi Abu Vulkanik Kelud dan Pupuk Kandang - Jauhari Syamsiyah; Widyas Rahina (Agrosains : Jurnal Penelitian Agronomi, 2017)
Volcanic ash actually need  agent like an organic matter to mineralized. The study aims is to determine the effect of volcanic ash of Kelud and manure on the availability of calcium in Alfisols, the absorbent of calsium and their status for peanuts growth.This is greenhouse experiment arranged in factorial completely randomized design with single treatment. The result have been analyzed with analysis of variance by F test at 5% and the average comparison test using DMRT at 5% than will continued with Pearson Corelation test for analyzing the relation of intervariable. The results showed that volcanic ash of Kelud eruption and manure treatment significantly on leaves, chlorophyll, nodules, weight of wet crop stover, pH, CEC, Ca-total and Ca plant tissue but no significant on height of peanuts, stover dry weight, exchangable Ca and Ca uptake.Volcanic ash of Kelud and manure are better used as ameliorant than as a planting media.